TEACHING ANECDOTE WRITING BASED ON THE 2016 REVISED CURRICULUM TO THE TENTH GRADERS OF SMKN 1 GONDANG SRAGEN - Rasyid Manshur; Sarwiji Suwandi; Suyitno Suyitno (Center of Language and Cultural Studies [CLCS], 2017)
This study describes: (1) process of writing anecdote text based on the 2016 revised curriculum conducted by Indonesian Language teachers to the tenth graders of SMKN 1 Gondang, Sragen, (2) problems in the process of writing, and 3) efforts to overcome the problems made by the teachers. This qualitative research uses case study approach. The data sources in this research were events (the process of writing anecdote text), informants (teachers and students), and documents (syllabus and lesson plan). The results show that teaching to write anecdote text based on the 2016 revised curriculum needs more in-depth evaluation in order to improve planning, implementation, and assessment. It is also based on the encountered obstacles occurred in the learning process. The evaluation should uncover concepts, regulations and national education objectives implied in the curriculum the schools should attain.